Arbitration - Rau, Alan Scott (Foundation Press, 2006)
The Third Edition is the most current Arbitration offering on the market, highlighting very recent developments such as the Supreme Court's 2006 decision in Cardegna v. Buckeye. It features an all new section on the increasingly topical subject of complex and multiparty arbitration, addressing in particular the emerging topic of classwide arbitrations. Another newly added section deals specifically with problems in transnational arbitration, making this book suitable for use in any course or seminar specifically devoted to international arbitrations